2017
DOI: 10.1002/acn3.439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes in the Friedreich ataxia clinical outcome measures study

Abstract: ObjectiveFriedreich ataxia (FA) is a progressive neuromuscular disorder caused by GAA triplet repeat expansions or point mutations in the FXN gene. FA is associated with increased risk of diabetes mellitus (DM). This study assessed the age‐specific prevalence of FA‐associated DM and its impact on neurologic outcomes.Research Design and MethodsParticipants were 811 individuals with FA from 12 international sites in a prospective natural history study (FA Clinical Outcome Measures Study, FACOMS). Physical functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
(56 reference statements)
1
10
1
2
Order By: Relevance
“…19 However, this is mainly in line with a recent published work about the relevance of diabetes in FRDA in an American cohort presenting 9% of adults and 3% of children with diabetes. 46 Of note, the only predictor for the presence of diabetes in patients with FRDA was higher SARA scores. Thus, we failed to confirm previous work showing associations between diabetes and the size of GAA trinucleotide expansion in the FRDA gene, 21,47 longer disease duration, and a younger age at onset.…”
Section: Discussionmentioning
confidence: 98%
“…19 However, this is mainly in line with a recent published work about the relevance of diabetes in FRDA in an American cohort presenting 9% of adults and 3% of children with diabetes. 46 Of note, the only predictor for the presence of diabetes in patients with FRDA was higher SARA scores. Thus, we failed to confirm previous work showing associations between diabetes and the size of GAA trinucleotide expansion in the FRDA gene, 21,47 longer disease duration, and a younger age at onset.…”
Section: Discussionmentioning
confidence: 98%
“…FRDA is associated with an increased risk of diabetes mellitus (DM). It has been previously established that DM is independently associated with worse functional status in FRDA [ 32 ], independently of GAA repeat length. In the present study we observed a worse neurological status in FRDA patients with DM, compared to non-diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“… 78 , 80 , 82 Also, a disproportionate share of individuals with later onset FRDA and diabetes will require insulin. 77 …”
Section: Specific Care Aspectsmentioning
confidence: 99%